2018
DOI: 10.1097/nan.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties Related to Peripheral Intravenous Access in Children in an Emergency Room

Abstract: This prospective study examined the characteristics of children admitted to a pediatric emergency department and the factors that influenced the successful establishment of peripheral intravenous (IV) access. Descriptive and correlational analysis was completed using a convenience sample of 89 patients. Peripheral IV access was successful in 95.7% of the children, and the first attempt at insertion was successful in 53% of the procedures. Factors influencing the success of peripheral IV access were the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 18 publications
0
27
1
3
Order By: Relevance
“…Several successive studies validated the DIVA score in different populations, and the PIVA procedure was performed mostly by staff nurses at emergency department settings. 4,9,10…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several successive studies validated the DIVA score in different populations, and the PIVA procedure was performed mostly by staff nurses at emergency department settings. 4,9,10…”
Section: Discussionmentioning
confidence: 99%
“…A literature survey revealed that all of these studies regarding DIVA have been conducted at pediatric emergency department or pediatric clinics, which is the main drawback of these reports. 4,9,10…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the characteristics of poor nutritional status, younger age, and lousy peripheral venous circulation, obtaining venous access can be challenging in children with cardiac anomalies. Cyanotic children are, in particular, tough to deal with [4][5][6]. Also, several articles [7,8] had reported an apparent high prevalence of Ehlers-Danlos syndrome, a severe heritable disorder of connective tissue in complex congenital heart defects, which may further deteriorate the peripheral venous conditions.…”
mentioning
confidence: 99%